The Impact of Esophageal Oncological Surgery on Perioperative Immune Function; Implications for Adjuvant Immune Checkpoint Inhibition - Donlon, Noel E.; Davern, Maria; Sheppard, Andrew D.; O’Connell, Fiona; Dunne, Margaret R.; Hayes, Conall; Mylod, Eimear; Ramjit, Sinead; Temperley, Hugo; Mac Lean, Michael; Cotter, Gillian; Bhardwaj, Anshul; et al. (Frontiers in Immunology, 2022)
Background: Immune checkpoint inhibitors (ICIs) are being investigated for their role as an adjunct in the multimodal treatment of esophageal adenocarcinoma (EAC). The most effective time to incorporate ICIs remains unknown. Our study profiles systemic anti-tumor immunity perioperatively to help inform the optimal timing of ICIs into current standards of care for EAC patients. Methods: Systemic immunity in 11 EAC patients was phenotyped immediately prior to esophagectomy (POD-0) and post-operatively (POD)-1, 3, 7 and week 6. Longitudinal serological profiling was conducted by ELISA. The frequency of circulating lymphocytes, activation status, immune checkpoint expression and damage-associated molecular patterns was assessed by flow cytometry. Results: The frequency of naïve T-cells significantly increased in circulation post-esophagectomy from POD-0 to POD-7 (p<0.01) with a significant decrease in effector memory T-cells by POD7 followed by a subsequent increase by week 6 (p<0.05). A significant increase in activated circulating CD27+ T-cells was observed from POD-0 to POD-7 (p<0.05). The percentage of PD-1+ and CTLA-4+ T-cells peaked on POD-1 and was significantly decreased by week 6 (p<0.01). There was a significant increase in soluble PD-1, PD-L2, TIGIT and LAG-3 from POD-3 to week 6 (p<0.01). Increased checkpoint expression correlated with those who developed metastatic disease early in their postoperative course. Th1 cytokines and co-stimulatory factors decreased significantly in the immediate post-operative setting, with a reduction in IFN-, IL-12p40, IL-1RA, CD28, CD40L and TNF-α. A simultaneous increase was observed in Th2 cytokines in the immediate post-operative setting, with a significant increase in IL-4, IL-10, IL-16 and MCP-1 before returning to preoperative levels at week 6. Conclusion: Our study highlights the prevailing Th2-like immunophenotype post-surgery. Therefore, shifting the balance in favour of a Th1-like phenotype would offer a potent therapeutic approach to promote cancer regression and prevent recurrence in the adjuvant setting and could potentially propagate anti-tumour immune responses perioperatively if administered in the immediate neoadjuvant setting. Consequently, this body of work paves the way for further studies and appropriate trial design is needed to further interrogate and validate the use of ICI in the multimodal treatment of locally advanced disease in the neoadjuvant and adjuvant setting.